An in vitro study of fracture resistance of weakened tooth roots reinforced with two types of adhesive restorative materials - Ahmad A.M.; Bakar W.Z.W.; Husein A.; Alam M.K. (Ibn Sina Trust, 2024)
Introduction: Composite resin (CR) is among the commonly used material for intraradicular reinforcement of weakened tooth roots. Purpose: This study was to compare the fracture resistance of experimentally weakened tooth roots reinforced using auto-polymerized composite resin and light-polymerized composite resin. Materials and Methods: Fifty-six extracted human maxillary incisors were divided into 2 groups (n = 28) and the root canals were over prepared to weaken it. The samples in Group A were restored using light-cured CR Z100 and light-transmitting polymerizing post (Luminex), whereas Group B using auto-cured CR Alpha-dent. Both groups were placed with metal parapost cemented with a resin luting cement (Nexus 2). Specimens were subjected to compressive load (N) using Instron machine until fracture. Data were submitted to independent t test analysis of variance (p < 0.05). Results: There was no significant difference (p = 0.233) in fracture resistance between the teeth reinforced with light-polymerizing and auto-polymerizing CR are 549.3 ( 95.44) and 490.7 ( 110.37) respectively. Conclusion: The use of less technique sensitive auto-polymerizing CR give equivalent benefit effect on reinforcing weakened roots, as the more commonly light-polymerized composite resin.